Respon Pertumbuhan, Hasil Dan Kualitas Hasil Tanaman Horenso (Spinacia oleraceae L.) Akibat Pengaruh Pupuk Organik Cair dan Kotoran Cacing (Kascing) - Wiwin Darwin; Raden Budiasih; Linlin Parlinah (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2024)
Response of Plant Growth, Yield and Yield Quality of Horenso (Spinacia oleraceae L.) as Effect by Liquid Organic Fertilizer and Vermicompost. Experimental Station of SMK PPN Gegerkalong Bandung West Java, with about 1100 metre above sea level and Andisols soil type order from September 2022 up to November 2022. Experiment was to Randomized Block Design (RBD) with factorial pattern two factors and two replications. The first factor was liquid organic fertilizer (P) rate consisted of five levels namely : p0 (0 mL L-1 water), p1 (2 mL L-1 water), p2 (4 mL L-1 water), p3 (6 mL L-1 water1), p4 (8 mL L-1 water). The second factors was vermicompost (C) rate consisted of five levels namely: c0 (0 g plant-1), c1 (30 g plant-1), c2 (60 g plant-1), c3 (90 g plant-1), and c3 (120 g plant-1). This interactions between liquid organic fertilizer rate and vermicompost rate on response of plant height at 30 days after planting (dap), weight of plant fresh, weight of plamt fresh bran, and yield of plant fresh per plot. Application of liquid organic fertilizer at 6 mL L-1 water and vermicompost 90 g plant-1 gave good effect better than other treatments.